2012
DOI: 10.1111/j.1744-6570.2012.01253.x
|View full text |Cite
|
Sign up to set email alerts
|

CEO Servant Leadership: Exploring Executive Characteristics and Firm Performance

Abstract: This study offers an examination of the relationships between chief executive officer (CEO) servant leadership, the executive characteristics of narcissism, founder status, and organizational identification, and firm performance in a sample of 126 CEOs in technology organizations. Analysis of data gathered over multiple periods revealed a negative relationship between CEO narcissism and servant leadership, and a positive relationship between founder status (i.e., founder or nonfounder) and servant leadership. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
300
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(317 citation statements)
references
References 86 publications
(181 reference statements)
11
300
2
4
Order By: Relevance
“…Narcissism is an increasingly popular topic in organizational research, as evidenced by several recent articles in top organizational journals (e.g., Galvin, Waldman, & Balthazard, 2010;Harms, Spain, & Hannah, 2011;Judge et al, 2006;Judge, Piccolo, & Kosalka, 2009;Nevicka, Ten Velden, De Hoogh, & Van Vianen, 2011b;O'Boyle, Forsyth, Banks, & McDaniel, 2012;Peterson, Galvin, & Lange, 2012;Wu & LeBreton, 2011). This recent research has documented the importance of narcissism by establishing its relation to workplace outcomes, particularly leadership and CWB.…”
Section: Potential Moderatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Narcissism is an increasingly popular topic in organizational research, as evidenced by several recent articles in top organizational journals (e.g., Galvin, Waldman, & Balthazard, 2010;Harms, Spain, & Hannah, 2011;Judge et al, 2006;Judge, Piccolo, & Kosalka, 2009;Nevicka, Ten Velden, De Hoogh, & Van Vianen, 2011b;O'Boyle, Forsyth, Banks, & McDaniel, 2012;Peterson, Galvin, & Lange, 2012;Wu & LeBreton, 2011). This recent research has documented the importance of narcissism by establishing its relation to workplace outcomes, particularly leadership and CWB.…”
Section: Potential Moderatorsmentioning
confidence: 99%
“…For example, a sample of CEOs from the technology sector revealed that narcissism negatively predicted servant leadership (a form of leadership that focuses on followers' needs and personal integrity), and that servant leadership subsequently predicted firm financial performance (Peterson et al, 2012). Other complementary research found that supervisors rate their narcissistic employees negatively on the interpersonal and ethical components of leadership, but narcissism was unrelated to task-specific components of leadership such as judgment and decision making (Blair et al, 2008).…”
Section: Narcissism and Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Servant leadership instruments have been used to examine the effect of servant leadership on diverse dependent variables such as job satisfaction [11,[17][18][19][20], organizational citizenship behavior [21,22], team performance [23,24], and firm performance [25]. This growing body of empirical research demonstrates the value of servant leadership not only as a positive ideal, but also as an effective approach to leadership practice.…”
Section: Servant Leadershipmentioning
confidence: 99%
“…Coinciding with business interest in a more caring and responsible style of leadership, organizational scholars have shifted their attention away from leadership based on individualistic, self-serving tendencies towards more relational styles of leadership (Avolio et al, 2009 as cited in Peterson & Galvin, 2012). There has been tremendous conceptual and empirical research that has focused on servant leadership (Peterson & Galvin, 2012). It is a leadership style that transcends self-interest to serve the needs of others by helping them grow professionally and personally (Lussier & Achua, 2007 as cited in Carder, 2012).…”
Section: Servant Leadershipmentioning
confidence: 99%